Social trust and the location choices of foreign firms in China–The moderating role of formal institution and cultural distance - Shen, Huiyun; Yi, Changjun; Yu, Jie; Gou, Jin (Frontiers in Psychology, 2023)
How to choose a right location in the host subnational region is one of the key decisions foreign firms need to make in the internationalization process. Using the sample of foreign firms’ location choices in China from 2008 to 2020 in Orbis Global Enterprise Database, this study finds that social trust positively related to the location choices of foreign firms in subnational regions. Our results also show that this positive effect is contingent on the formal institution and the cultural distance between home and host country. When the formal institution is strong and the cultural distance between home and host country is high, social trust has a more significant positive impact on the location choices of foreign firms in subnational regions. Besides, the results show that cost advantage, information advantage and innovation advantage are important mechanisms for social trust to influence foreign firms' location choices in subnational regions. Unlike prior studies based on country-level formal institutions in location choices, through analyzing the social trust in subnational regions on location choices of foreign firms, this study highlights the importance of incorporating informal institutions at the subnational level in examining strategies.